2009
DOI: 10.1097/mog.0b013e328317c897
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vaccines and pathogenesis: 2008

Abstract: Purpose of Review-Rotaviruses cause life-threatening gastroenteritis in children throughout the world. The burden of disease has resulted in the development of two live, attenuated vaccines that are now licensed in many countries. This review summarizes new data on these vaccines, their effectiveness, and remaining challenges including new data on the rotavirus enterotoxin, a potential antiviral target.Recent findings-Live attenuated rotavirus vaccines are used to protect infants against severe rotavirus-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Rotaviruses are etiological agents of severe dehydrating diarrhea in infants and young children and cause nearly 600,000 deaths globally every year (34). Rotaviruses are nonenveloped icosahedral members of the family Reoviridae and contain 11 segments of genomic double-stranded RNA (dsRNA) within a triple-layered particle.…”
mentioning
confidence: 99%
“…Rotaviruses are etiological agents of severe dehydrating diarrhea in infants and young children and cause nearly 600,000 deaths globally every year (34). Rotaviruses are nonenveloped icosahedral members of the family Reoviridae and contain 11 segments of genomic double-stranded RNA (dsRNA) within a triple-layered particle.…”
mentioning
confidence: 99%
“…14 subsequently vaccines such as Rota Teq and Rotarix have been developed. 15 The Clinical Presentation having typical triad of severe intermittent abdominal pain, currant jelly stools and vomiting is seen in less than 20% of cases. 16 Bouts of abdominal pain may be evidenced by pulling of knees against the abdomen with an interim asymptomatic healthy child.…”
Section: Discussionmentioning
confidence: 99%
“…Here, expression of the rotavirus enterotoxin (NSP4) was carried out before and after removal of its diarrhea-inducing domain in E. coli BL21 DE3. As this protein is made of different domains with distinct functions (3), it has been subject of different studies in full-length, modified, truncated, and mutated forms (5,9,17,21). This protein is toxic for both prokaryotic and eukaryotic (especially mammalian) cells because of disruption of calcium homeostasis and membrane destabilization (29,35).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the integrins α1β1 and α2β1 are receptors for NSP4 in which amino acids 114-130 are responsible for binding to the I domain of α1; and residues 114-135 can block binding of the natural ligand, collagen I, to Integrin α2 (8). This interaction in turn leads to secretion of chloride ions and diarrhea-induction via a phospholipase C (PLC) mediated pathway (9). Therefore, it can be suggested that removing amino acids 114-135 could effectively lower, if not inhibit, the toxicity of NSP4 for two reasons: first, via disrupting the correct functional conformation and oligomerization of the protein and second, via blocking the interaction of NSP4 with integrin receptors.…”
mentioning
confidence: 99%